The correlation between score-based protocol for equine joint assessment and subsequent arthroscopic intervention outcomes - Silva, Marilene Machado; Hagen, Stefano Carlo Filippo; Vendruscolo, Cynthia Do Padro; Baccarin, Raquel Yvonne Arantes; Spagnolo, Júlio David; Yamada, Ana Lúcia Miluzzi; Stievani, Fernanda de Castro [UNESP]; Silva, Luis Claudio Lopes Correia da (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
This study aimed to grade joint abnormalities in horses submitted to therapeutic arthroscopy using score-based protocols for equine joint assessment, correlated with arthroscopic treatment outcomes and owner satisfaction. In this prospective study, we evaluated 126 joints of athletic horses referred for arthroscopy. The joints were scored according to findings of medical history and physical, radiographic, ultrasonographic and arthroscopic examination. Lameness, positive response to flexion test and decreased maximum joint flexion angle were detected in more than 50% of joints. Soft tissue swelling, sclerosis, subchondral bone osteolysis and single osteochondral fragments were the most common radiographic findings. Ultrasonographic examination revealed changes in synovial fluid volume and appearance, and subchondral bone irregularities. Increased vascularity of the synovial villi, chondral fibrillation, chondral fissures and superficial cartilage erosions were the most significant arthroscopic findings. The approaches that demonstrated greater sensitivity and correlation with treatment outcome and owner satisfaction were medical history, ultrasonographic and arthroscopic examination. The scoring protocol employed to grade joint abnormalities enabled the creation of a joint score system for the objective assessment, thus determining the most frequent findings and establishing an injury severity score for each joint.
Protocolo de avaliação baseado em escore das afecções articulares em equinos e correlação com o resultado do tratamento por artroscopia
Keywords: Arthroscopy; Joint; Radiography; Score; Ultrasonography